The harmonization of civil and commercial law in Europe - Pasa, Barbara (Central European University Press, 2005)
Annotation "This volume seeks to frame the creation of a new European Common Law in the context of recent events in European integration, and although acting independently, it represents the second book in A Guide to European Private Law."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved